La science et l'hypothese - Poincaré, Henri 1854-1912; Vuillemin, Jules 1920-2001 (Paris Flammarion, 1968)
'La Science et l'Hypothèse', aimed at a non-specialist readership, deals with mathematics, space, physics and nature. It puts forward the theses that absolute truth in science is unattainable, and that many commonly held beliefs of scientists are held as convenient conventions rather than because they are more valid than the alternatives.In this book, Poincaré describes open scientific questions regarding the photo-electric effect, Brownian motion, and the relativity of physical laws in space. Reading this book inspired Albert Einstein's subsequent Annus Mirabilis papers published in 1905.
Jules Henri Poincaré (1854-1912) was a French mathematician, theoretical physicist, engineer, and philosopher of science. He is often described as a polymath, and in mathematics as "The Last Universalist", since he excelled in all fields of the discipline as it existed during his lifetime.
Originally published in 1902.
Keywords: 20th Century (1901-2000); Science; Philosophy; France